Granulomatosis with Polyangiitis as a Cause of Sudden-Onset Bilateral Sensorineural Hearing Loss: Case Report and Recommendations for Initial Assessment. (21st April 2021) - Ratmeyer, Paul R.; Johnson, Benjamin R.; Roldan, Luis P.; Kraai, Tania L.
Abstract : Granulomatosis with polyangiitis (GPA) is a severe systemic vasculitis that commonly affects the paranasal sinuses, upper and lower respiratory tracts, and kidneys. GPA has also been associated with sensorineural hearing loss (SNHL), through inflammation of the cochlear apparatus. Early recognition, diagnostic laboratory evaluation, and appropriate treatment are essential to improve outcomes and achieve remission for patients with GPA. Here, we present a case of bilateral sudden sensorineural hearing loss (SSNHL) and distal symmetric polyneuropathy as the first presenting signs of GPA. A specific diagnostic work-up to rule out autoimmune inner-ear disease in patients with bilateral SSNHL is not clearly stated in the clinical practice guidelines from the American Academy of Otolaryngology-Head and Neck Surgery. The aim of this paper is to delineate an appropriate diagnostic work-up for patients with bilateral SSNHL when there is concern for autoimmune disease.